The Rise of Tahfiz Schools in Contemporary Indonesia - Jahroni, Jajang (Studia Islamika, 2024)
This article discusses the rise of tahfiz schools in contemporary Indonesia which were pioneered by the Salafis and PKS-affiliated groups (PAGs). While tahfiz has been preserved for centuries among traditionalist Muslims, the tahfiz schools the Salafis and the PAGS promoted were integrated into school systems that also offer sciences. As a result, tahfiz schools are popular among urban Muslims who expect their children to be able to read the Holy Quran better while at the same time equipping them with sciences. This allows them to enroll at public universities. Even though tahfiz schools are relatively expensive, they never lacked students. Small, middle-size, and large tahfiz schools have been established across the country and exclusive tahfiz schools are equipped with libraries, gyms, computer labs, laundry facilities, cafés, and theatres. These facts have changed the long-established image of madrasa and Islamic schools which were seen as rural and poorly organized. The commodification of Islam is eventually inevitable and tahfiz schools have become an integral part of this process. They have become an important political issue since the 2010s.